PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK - Rosfadhila, Hani (2015)
The students' learning outcomes within cognitive field, particularly in knowleadge understanding and application skills are crucially needed in order to create a productive generation. The aim of this research is to find out the how effective is the application of creative-productive learning strategy to improve the learning outcomes of the 11th-graders' school year of 2014-2015 in Wahidin Vocational High School Cirebon. Quantitative approach been used to conduct this research with pre-experimental design as the experiment method and one group pretest-posttest design for the research design. The data-revealer tool that used in this research are C1, C2, C3 cognitive learning outcome questions as well as questionnaires. The result of the research comes up with (1) there are significant differences learning outcomes between the lower class and the upper class, the lower class and the middle class and (2) allmost all students give a postive response about interactive multimedia-based creative-productive learning strategy. Keywords: Learning Outcomes, Creative-Productive Learning Strategy Hasil belajar siswa yang dalam ranah kognitif khususnya dalam kemampuan pengetahuan, kemampuan pemahaman dan kemampuan aplikasi sangat di perlukan dalam menciptakan generasi yang produktif. Tujuan penelitian ini untuk mengetahui keefektifan penerapan strategi pembelajaran kreatif-produktif untuk meningkatkan hasil belajar siswa kelas XI SMK Wahidin Cirebon Tahun Ajaran 2014-2015. Pendekatan penelitian yang digunakan adalah kuantitatif dengan metode eksperimen pre-experimental design dan desain penelitian one-group pretest-posttest design. Alat pengungkap data yang digunakan adalah soal hasil belajar ranah kognitif C1, C2, C3 dan angket. Hasil penelitian berupa : (1) terdapat perbedaan signifikan terhadap hasil belajar peserta didik kelas atas dan kelas bawah, serta kelas atas dan kelas tengah dan (2) hampir seluruh siswa memberikan respon positif terhadap strategi pembelajaran kreatif produktif berbasis multimedia interaktif. Kata kunci: Hasil Belajar, Strategi Pembelajaran Kreatif-Produktif.